Endurance, resistance and resilience in the South African health care system: case studies to demonstrate mechanisms of coping within a constrained system. Issue 1 (June 2015) - Eyles, John; Harris, Bronwyn; Fried, Jana; Govender, Veloshnee; Munyewende, Pascalia
Abstract Background South Africa is at present undertaking a series of reforms to transform public health services to make them more effective and responsive to patient and provider needs. A key focus of these reforms is primary care and its overburdened, somewhat dysfunctional and hierarchical nature. This comparative case study examines how patients and providers respond in this system and cope with its systemic demands through mechanisms of endurance, resistance and resilience, using coping and agency literatures as the theoretical lenses. Methods As part of a larger research project carried out between 2009 and 2010, this study conducted semi-structured interviews and observations at health facilities in three South African provinces. This study explored patient experiences of access to health care, in particular, ways of coping and how health care providers cope with the health care system's realities. From this interpretive base, four cases (two patients, two providers) were selected as they best informed on endurance, resistance and resilience. Some commentary from other respondents is added to underline the more ubiquitous nature of these coping mechanisms. Results The cases of four individuals highlight the complexity of different forms of endurance and passivity, emotion- and problem-based coping with health care interactions in an overburdened, under-resourced and, in some instances, poorly managed system. Patients' narratives show the micro-practices they use to cope with their treatment, by not recognizing victimhood and sometimes practising unhealthy behaviours. Providers indicate how they cope in their work situations by using peer support and becoming knowledgeable in providing good service. Conclusions Resistance and resilience narratives show the adaptive power of individuals in dealing with difficult illness, circumstances or treatment settings. They permit individuals to do more than endure (itself a coping mechanism) their circumstances, though resistance and resilience may be limited. These are individual responses to systemic forces. To transform health care, mutually supportive interactions are required among and between both patients and providers but their nature, as micro-practices, may show a way forward for system change.